Impact of polysorbate 80 on the antimicrobial activity of oregano and thyme - Carvalho, Marta (2025)
Plant-derived essential oils (EOs) possess significant antimicrobial potential against spoilage and pathogenic microorganisms. However, their efficacy can vary depending on the test method, making it difficult to standardise results. This study aimed to investigate the effect of polysorbate 80, a common surfactant used to emulsify EOs, on antimicrobial activity and minimum inhibitory concentration (MIC) determinations. The antimicrobial activity of oregano and thyme EOs was tested against 40 microorganisms with and without the presence of polysorbate 80. Antimicrobial activity was qualitatively assessed using the disc diffusion assay (DDA) and quantitatively via broth microdilution to determine MIC values. Both oregano and thyme EOs exhibited antimicrobial activity against all tested microorganisms in the DDA, regardless of the surfactant’s presence. However, MIC determinations revealed that higher EO concentrations were required to inhibit microbial growth when polysorbate 80 was included in the emulsification process. These findings indicate that polysorbate 80 influences antimicrobial test results by reducing EO efficacy while enhancing solution homogeneity and handling in aqueous media. The study highlights the critical role of emulsifiers in antimicrobial testing, as their use can significantly impact the interpretation of results and the perceived effectiveness of EOs in food preservation, pharmaceuticals, and other applications.